2011
DOI: 10.1155/2011/501396
|View full text |Cite
|
Sign up to set email alerts
|

Porcelain Atrium: A Case Report with Literature Review

Abstract: Massive left atrial wall calcification, or porcelain atrium, is very rare. We describe a case of an unusual pattern of cardiac calcification demonstrated on routine preoperative chest X-ray for cataract surgery in a 71-year-old Nigerian woman. Past medical history was significant for mitral stenosis and atrial fibrillation. Radiographic imaging revealed curvilinear high density areas of calcification outlining the left atrium on the chest X-ray. Noncontrast CT scan of the thorax confirmed the left atrial distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…If the heavy calcification was observed in the left atrial appendage, the atrial free wall, and the mitral valve apparatus, the term ''porcelain atrium'' is used [1,[8][9][10]. The interatrial septum is usually spared, and this allows surgical approaches to the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the heavy calcification was observed in the left atrial appendage, the atrial free wall, and the mitral valve apparatus, the term ''porcelain atrium'' is used [1,[8][9][10]. The interatrial septum is usually spared, and this allows surgical approaches to the mitral valve.…”
Section: Discussionmentioning
confidence: 99%
“…Although calcification of the left atrium is relatively common in the setting of long-lasting rheumatic valve disease, massive calcification of the left atrium, also known as ''porcelain atrium [1],'' ''coconut atrium [2],'' or ''mold-like calcification [3],'' is a rare condition. The left atrial calcification is described as a high-density ring encircling the left atrium on chest X-ray.…”
Section: Introductionmentioning
confidence: 99%
“…During atherogenesis, endothelial dysfunction plays an important role in vascular calcification. Several investigators have demonstrated that the endothelium is a source of osteoprogenitor cells in vascular calcification [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Further inflammation during the healing process of rheumatic carditis may be involved in the pathogenesis of rheumatic heart disease.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Indeed, atrial fibrillation of many years duration is almost universal. The advanced electro anatomical remodeling of the left atrium exacerbates the hemodynamics of heart failure; ii) the consensus of other group of investigators is that left atrial calcification is the end-result of repeated and extensive rheumatic auricularis beginning with focal patches of calcification in areas of rheumatic endocardial ulceration and progression to chronic fibrotic changes with plaques of subendocardial calcium [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The incidence of atrial calcification appears to be related to the severity of the original rheumatic attack and the associated valvular damage.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation